Cellular and humoral immunity to Ebola Zaire glycoprotein and viral vector proteins following immunization with recombinant vesicular stomatitis virus-based Ebola vaccine (rVSVΔG-ZEBOV-GP). Issue 8 (17th February 2023) - Raabe, Vanessa; Lai, Lilin; Morales, Juliet; Xu, Yongxian; Rouphael, Nadine; Davey, Richard T.; Mulligan, Mark J.
Abstract: While effective at preventing Zaire ebolavirus (ZEBOV) disease, cellular immunity to ZEBOV and vector-directed immunity elicited by the recombinant vesicular stomatitis virus expressing ZEBOV glycoprotein (rVSVΔG-ZEBOV-GP) vaccine remain poorly understood. Sera and peripheral blood mononuclear cells were collected from 32 participants enrolled in a prospective multicenter study [ClinicalTrials.gov NCT02788227] before vaccination and up to six months post-vaccination. IgM and IgG antibodies, IgG-producing memory B cells (MBCs), and T cell reactivity to ZEBOV glycoprotein (ZEBOV-GP), vesicular stomatitis virus-Indiana strain (VSV-I) matrix (M) protein, and VSV-I nucleoprotein (NP) were measured using ELISA, ELISpot, and flow cytometry, respectively. 11/32 (34.4%) participants previously received a different investigational ZEBOV vaccine prior to enrollment and 21/32 (65.6%) participants were ZEBOV vaccine naïve. Both ZEBOV vaccine naïve and experienced participants had increased ZEBOV-GP IgG optical densities (ODs) post-rVSVΔG-ZEBOV-GP vaccination while only ZEBOV vaccine naïve participants had increased ZEBOV-GP IgM ODs. Transient IgM and IgG antibody responses to VSV-I M protein and NP were observed in a minority of participants. All participants had detectable ZEBOV-GP specific IgG-producing MBCs by 6 months post-vaccination while no changes were observed in the median IgG-producing MBCs to VSV-I proteins. T cell responses to ZEBOV-GP differed between ZEBOV vaccine experienced and ZEBOV vaccine naïve participants. T cell responses to both VSV-I M protein and VSV-I NP were observed, but were of a low magnitude. The rVSVΔG-ZEBOV-GP vaccine elicits robust humoral and memory B cell responses to ZEBOV glycoprotein in both ZEBOV vaccine naïve and experienced individuals and can generate vector-directed T cell immunity. Further research is needed to understand the significance of pre-existing vector and target antigen immunity on responses to booster doses of rVSVΔG-ZEBOV-GP and other rVSV-vectored vaccines.